PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. RICKY KENCANA SUKSES MANDIRI PALEMBANG - Yofrizal Heralkan; Kholillah; Bora Alviolesa (Prodi Bisnis Digital Fakultas Ekonomi Dan Bisnis, 2025)
This study aims to determine the influence of the work environment and discipline on employee performance at PT. Ricky Kencana Sukses Mandiri simultaneously and partially. The study used an associative approach, with the variables being the work environment, employee discipline, and performance. A sample of 111 respondents was drawn using a simple random sampling method. The primary data used was primary data using a questionnaire. The analysis technique used was multiple linear regression, F-test and t-test, and the coefficient of determination. The results of the multiple linear regression indicate that the work environment and work discipline have a positive effect on employee performance. The results of the simultaneous hypothesis test indicate that the work environment and work discipline significantly influence employee performance at PT. Ricky Kencana Sukses Mandiri Palembang. Partially, the work environment and work discipline significantly influence employee performance. The coefficient of determination indicates that the work environment and work discipline contribute 49.3% to the fluctuations in employee performance.